Greenhouse gas emissions in Kenya's crop sector: A policy analysis report - Ndetu, Veronica; Kioko, Angela; Kinyua, Ivy; Jalango, Dorcas; Nyawira, Sylvia (2024)
Agriculture accounts for one-third of global greenhouse gas (GHG) emissions, arising from crop and livestock activities, land-use changes, and related processes. Addressing climate change in agriculture necessitates solutions that yield economic benefits, improve livelihoods, and protect the environment. The United Nations Framework Convention on Climate Change (UNFCCC) requires all Parties to report their GHG emissions and actions to the Conference of the Parties (COP) through national inventories. The Intergovernmental Panel on Climate Change (IPCC) guidelines ensure these inventories are comparable, accurate, and reflective of actual emission changes. Decision 18/CMA.1 established the modalities and principles for the enhanced transparency framework, categorizing reporting methods into tiers based on complexity. For agriculture and land-use sectors, higher-tier methods, which use national data and models, are more accurate but require better understanding and resources.